Perlindungan Hukum Bagi Pelaku Usaha Terhadap Tindak Pidana Penipuan dalam Transaksi Jual Beli Online (Studi Kepolisian Resor Kota Besar Medan) - Wydhea Eikel Primsa Kaban; Sri Hidayani; Ridho Mubarak (Universitas Medan Area, 2023)
Technology has developed very quickly and rapidly in this day and age. Therefore, qualified legal protection is needed for business actors from online-based criminal acts of fraud. The purpose of this study is to find out legal protection efforts for business actors against criminal acts of fraud in online transactions carried out at the Medan Polrestabes; as well as obstacles that occur in the disclosure of criminal acts of online transaction fraud. This research is normative juridical law research, namely research conducted based on secondary data. The nature of this research is descriptive analysis. The data used in this research is secondary data, namely data obtained from library research in the form of legal materials. Data collection techniques, namely literature and field. The research results show that efforts to provide business actors with legal protection in the form of compensation and/or sanctions if business actors do not receive compensation, because the consumer protection law does not specifically determine criminal penalties or sanctions for consumers who commit crimes.